PENGARUH MANTIQ (LOGIKA) DALAM PENGEMBANGAN ILMU-ILMU KEISLAMAN - Edwin Syarif (ILMU USHULUDDIN, 2016)
In the golden age of Islamic civilization, science was well developed. The developed sciences are not only Islamic sciences which are the study of Al-Qur'an and Hadith texts, but also other sciences including: Astronomy, al-Jabar, Chemistry, Physics. Especially in the Islamic sciences, the influence of the use of Mantiq is quite large, so that it has produced many qualified scientists and works. This fact, of course, cannot be separated from the persistence of the scholars in giving spirit to the teachings of Islam itself, so that nothing escapes their discussion. Several verses are classified into one type, although trying to be scattered everywhere to be organized into one field of science. The legal verses are grouped into one and then arranged systematically, which then becomes ushul fiqh and fiqh. If traced further, the steps taken in the development of Islamic sciences will be found that Islamic philosophy has a significant role in the beginning of Islamic sciences, especially mantiq. Mantiq or by another name Logic since its appearance in Greece has experienced great development and influence in human life. Logic itself has developed from traditional logic to symbolic logic. This development is in line with changes in human thinking. Logic is influential in shaping a science. The study of the influence of Mantiq on the development of Islamic sciences is a necessity so that it can be an evaluation of the development of Islamic scholarship in the future. Mantiq, which is the form and rules of rational thinking, is identical to the modern way of thinking. Therefore, by looking at the influence of Mantiq on Islamic sciences in the past, we will be able to ask the question whether Mantiq science with the principles of thinking in the past is still relevant to current scientific developments. There are four Mantiq principles used in this study, namely: Syllogism, Deductive, Inductive and Analogy / Qiyas. These four principles are used in analyzing Islamic sciences in general, namely: Tafsir, Ushul Fiqh, and Kalam. The results of the analysis become input for the development of Islamic sciences in general.